Improving thermal conductivity of poly(vinyl alcohol) composites by using functionalized nanodiamond. (February 2021) - Li, Linhong; Qin, Yue; Wang, Hao; Li, Maohua; Song, Guichen; Wu, Yuming; Wei, Xianzhe; Ali, Zulfiqar; Yi, Jian; Song, Shulin; Lin, Cheng-Te; Jiang, Nan; et al.
Abstract: Highly thermally conductive polymer composites with over 10 W m −1  K −1 are widely pursued in the commercial field. Unfortunately, the polymer composites with high thermal conductivity are few reported using simple and scalable methods to meet the commercial demands. Therefore, herein highly thermal conductive polymer composites consisting of hydroxyl-rich nanodiamonds (ND-OH) and poly(vinyl alcohol) (PVA) are reported, which exhibits the interfacial properties of composite is closely related to its thermal conductivity. It proves that interface strength between matrix and filler would dominate the thermal conductivity of composite at a relatively low content. While the thermal conductivity would be dominated by the filler-filler interaction at high loadings. The ultrahigh thermal conductivity of the PVA/ND-OH composite is 18.98 W m −1  K −1 when ND-OH reach at 90 wt%. The polymer composites present the excellent thermal conductivity and show a potential application for thermal management of the next-generation electronic products. Graphical abstract: Image 1 Highlights: Hydroxyl-rich nanodiamond was prepared. The addition of filler will change the interface properties of the composite. Interface strength would dominate the thermal conductivity of composite. The thermal conductivity of composite reach at 18.98 W m −1 K −1 .